Permeability & characterization study of (polylactic acid) PLA-modified NA+ nanocomposites for packaging application - Siti Amirah, Nor Effendi (2013)
One of the most versatile polymers is poly-lactic acid (PLA) which is well known as its biodegradable, high molecular weight, aliphatic polyester derived from renewable resources which is environmentally benign and good processability. In this study, a series of PLA nanocomposite with a different percentage of modified Na+ with an addition of Polyethylene glycol (PEG) were prepared using the solution intercalation method. The modification of Na+ was done via an ion exchange method by using Copper (II) Chloride as an ion exchange solution with different type of solvent which are water, ethanol and methanol. The existence of the ion exchange between the modifications was confirmed through Atomic Absorption Spectrometry (AAS). The structure of the polymer was examined through X-Ray Diffraction (XRD) while their morphology was illustrated by Scanning Electron Microscopy (SEM). The modification of the Na+ for every type of solvent was found to be successful where they show their existence of the Transition Metal Ions (TMIs) through AAS and the highest d-spacing was obtained in methanol through XRD with d=14.74 Å. A barrier properties of the film were examined to investigate the amount of water vapor transmit per unit area and time. The permeability of the film was found to decrease with the increase of Na+ content since 3% of the clay content without an exhibition of Polyethylene Glycole (PEG) shows the lowest Water Vapor Transmission Rate (WVTR). An exfoliation behavior was also found in the structure of PLA with 3% of the clay without the presence of PEG with no peak was detected through XRD.This study indicates that PLA with a modified Na+ as a filler is better than pure matrix in terms of structure, barrier properties and configuration also could be served as effective nanocomposite for packaging application.